Utilization of Bottom Ash for Clay Mine Rehabilitation - Suloshini, S.; Ranathunga, A.S.; Kulathilaka, S.A.S.; Gunawardana, W.B.; Mapa, M.M.S.T.M. (IEEE, 2022)
Attheendofminingactivities,claymineswereabandonedduetothecost andnon-availabilityoffillingmaterials.Theseabandonedclayminescauseadverse environmentalandsocialimpacts.Inaddition,largequantitiesofbottomash(BA) aregeneratedasaby-productofcoalcombustionprocess.ThisBAisdisposedby opendumpinginthelands,whichcreatessevereenvironmentalpollution.Therefore, conductedresearchonutilizationofBAforminerehabilitationisbeneficial.The mainfocusofthisresearchisapplicabilityofBAgeneratedfromLakvijayapower plant,SriLankaasapotentialbackfillmaterialandasoilamendmentduringtheclay minerehabilitation.Initiallytestswereconductedtoinvestigatethebasicproperties ofBA.Next,chemicalcompositionofBAwasanalysedtoselectthesuitablecrops forvegetation.FurtherpH,electricalconductivityandwaterholdingcapacitywere checkedandmicrostructuralmorphologyofBAwasdeterminedthroughScanning ElectronMicroscope.TheresultsshowedthatBAhasgoodengineeringproperties andthepotentialtoimproveagronomiccharacteristicsofsoil.Ithasbetterwater holdingcapacityandpermeability.BAcanadjustsoilpHtoadesirableplantgrowth range.AsBAhasaveryporousstructure,therootsystemcaneasilydevelopand helpstouptakenutrientsbytheplant.However,aconsiderablepercentageoftrace metalsisaccumulatedinBAwhichwillincreasethebioavailabilityofsometrace metalstolevelsthatposesrisktohuman.Thus,investigationswerecarriedoutto identifytheheavymetalconcentrationinleachateofBAusingcolumnleachingtest. ResultsshowedthatleachabilitypotentialoftracemetalsinBAdoesnotexceedthe allowablelimits.
Keywords: Bottom ash; Clay mines; Compaction; Soil amendment; Trace metals